Implementation of the world health organization hand hygiene improvement strategy in critical care units - Mazi, Waleed (BioMed Central, 2013)
BACKGROUND: To determine hand hygiene compliance before and after an intervention campaign in critical care units, this study was carried out in the Intensive care unit (ICU), Neonatal intensive care unit (NICU), Burns unit (BU) and the Kidney unit of the King Abdul Aziz Specialist Hospital, Taif, Saudi Arabia. The observation using the WHO hand hygiene protocol took place in four phases with phase I, between April 24-May 06 2010 and phase II from May 29-June 09 2010. An educational intervention took place between the Phases I and II. Follow-up Phases III and IV were from 01–15 October 2010 and 15–30 March 2011 respectively. FINDINGS: 1,975 hand hygiene opportunities comprising of 409 in Phase I, 406 in Phase II, 620 in Phase III and 540 Phase IV were observed. Compliance rate was 67% pre-intervention, 81% in phase II, declining to 59% and 65% in phases III and IV. Increased compliance in the ICU from 39% in Phase I to 81% in Phase IV (p < 0.05) was sustained throughout the study. Highest compliance rates were recorded among nurses in all phases. The improved compliance for physicians observed in the post-intervention phase was lost in follow-up phases. Missed opportunities for hand hygiene were before patient contact, after touching patient’s surrounding and before aseptic techniques. Team-work and leadership were identified as enhancing factors for compliance. CONCLUSION: The WHO hand hygiene strategy combined with health education, continuous evaluation and team approach resulted in increased compliance but this was not sustained in certain critical care areas.